Uso dos n-alcanos em comparação ao método convencional para determinar a digestibilidade de nutrientes de fenos em equinos - Ribeiro, Leonir Bueno (2008)
The objective was to verify the viability use of n alkanes as internal markers in horses. There were used six adult males horses in a Latin square design (6x6) housed in cages of metabolism. The treatments consisted of levels of inclusion of Tifton 85 Hay and Alfalfa Hay, of which 100% Hay Tifton + 0% alfalfa hay (100T), 80% Hay Tifton + 20 % alfalfa hay (80T:20A), 60% Tifton Hay + 40% alfalfa hay (60T:40A); 40% Tifton Hay + 60% alfalfa hay (40T:60A), 20% Tifton Hay + 80% alfalfa hay (20T:80A) Tifton Hay and 0% + 100% alfalfa hay (100A). Later, there were evaluated the apparent digestibility coefficients (CDAp), digestibility coefficient with the use of n alkanes (CDalc) and digestibility coefficient with the use of n-alkanes corrected for fecal recovery (CDalcNC). There was a predominance of alkanes with greater length of carbon chains and the odd numbers in relation to even. For the percentage of fecal recoveries of n-alkanes it is observed that the alkanes, C30, C31, C32, C33, C35 and C36, showed the highest values (P <0.05). For nutrients digestibility there are significant differences for means comparison considering the choice of alkanes (P< 0.05).. In the equine the fecal recovery of n-alkanes, increased with increasing the length of chain carbonic (P< 0.05), but the fecal recovery was not complete possibly indicating that the n-alkanes degradation throughout the gastrointestinal tract, then recommending the correction to achieve the estimative The digestibility calculus were done using the total collect data and n-alkanes technique. The n-alkane technique overestimates the roughages nutrient diets digestibility coefficient. The nutrition diet quality could influence in the result using this technique. The n-alkane technique do not shown viability to utilization in equine tests, because of the reduced recovery tax and the elevate cost.